Pelatihan Pembuatan Bakso Ikan Tengiri untuk Pemberdayaan Ekonomi Jemaat GIA Lobak - Christina, Odilia Dea; Putra Perdana, Danis; Mahesa Yudhantara, Sandi; Febriyanto, Yahya (Al-Khidmah Jurnal Pengabdian Masyarakat, 2026)
This community service program (PkM) aimed to empower the youth and congregation of the Isa Almasih Lobak Church in Semarang by leveraging local fishery potential, specifically mackerel, to improve their economic self-reliance. The program was initiated due to the low selling price of fresh fish and the community's lack of knowledge and skills in processing it into value-added products. The method employed was a participatory and holistic approach, starting with a focus group discussion (FGD) to build commitment and identify needs. This was followed by training sessions on technical aspects of fish meatball production, basic financial management, and digital marketing strategies. The main results of the program demonstrated a significant increase in the partners' capacity. Participants successfully mastered hygienic and consistent meatball production techniques and adopted simple technology. Furthermore, they were able to implement basic digital bookkeeping and apply branding and marketing strategies through social media. Overall, this program successfully established a foundation for a sustainable fish meatball business, creating new economic opportunities and enhancing the self-reliance of the partner community by integrating technical, managerial, and marketing skills.